Exclusive and dissociative J/ψ photoproduction, and exclusive dimuon production, in p-Pb collisions at √SNN = 8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; López, Jorge; et al. (Physical review, 2023)
The ALICE Collaboration reports three measurements in ultraperipheral proton-lead collisions at forward rapidity. The exclusive two-photon process γγ → μþμ− and the exclusive photoproduction of J=ψ are studied. J=ψ photoproduction with proton dissociation is measured for the first time at a hadron collider. The cross section for the two-photon process of dimuons in the invariant mass range from 1 to 2.5 GeV=c2 agrees with leading-order quantum electrodynamics calculations. The exclusive and dissociative cross sections for J=ψ photoproductions are measured for photon-proton center-of-mass energies from 27 to 57 GeV. They are in good agreement with HERA results.
The ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, A. Lopez, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1014 weitere Personen]
Gesehen am 12.11.2024
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol